Sex‐Specific Effects of Myo‐Inositol Ingested During Lactation in the Improvement of Metabolic Health in Adult Rats. Issue 11 (5th May 2021) - Castillo, Pedro; Palou, Mariona; Otero, David; Núñez, Paula; Palou, Andreu; Picó, Catalina
Abstract: Scope: To examine the effects of myo‐inositol supplementation during lactation in male and female rats on metabolic parameters and its potential to reverse metabolic alterations associated with a moderate gestational calorie restriction. Methods and results: The offspring of control and 25% gestational calorie‐restricted rats are supplemented with myo‐inositol or vehicle throughout lactation and exposed to a Western diet (WD) from 5 to 7 months of age. Blood parameters are measured and gene expression and protein levels in retroperitoneal white adipose tissue (rWAT) and liver are analyzed. In male offspring, but not in females, myo‐inositol supplementation resulted in lower fasting triglyceride and insulin levels and HOMA‐IR at 7 months, and reversed the alterations in these parameters due to gestational calorie restriction. The expression pattern of key genes in metabolism in rWAT and liver support the beneficial effect of myo‐inositol supplementation in reversing metabolic alterations programmed by gestational calorie restriction in male rats. Conclusions: Myo‐inositol supplementation at physiological doses during lactation improves metabolic health and prevents the programmed trend to develop insulin resistance and hypertriglyceridemia in male rats acquired by inadequate fetal nutrition and exacerbated by a diabetogenic diet in adulthood. The absence of clear effects in females deserves further investigation. Abstract : Myo‐inositol supplementation at physiological doses during the suckling period improves later metabolic health in male rats. It also reverses most of the programmed trend to develop insulin resistance and hypertriglyceridemia acquired by inadequate fetal nutrition and exacerbated by a diabetogenic diet in adulthood. This can be explained by changes in the expression pattern of metabolism‐related genes and proteins in key tissues. The absence of clear effects in females deserves further investigation.